An extraordinary new species of melanophryniscus (anura, bufonidae) from Southeastern Brazil - Peloso, Pedro L.V. (2012)
We describe a new species of bufonid from a lowland, sandy soil, restinga habitat in the state of Espírito Santo, southeastern Brazil. Based on the shared occurrence of putative morphological synapomorphies of Melanophryniscus and the results of a phylogenetic analysis of DNA sequences of a broad sample of bufonids, and other anurans, we assign the new species to Melanophryniscus. The new species possesses several peculiar character states that distinguish it from all other Melanophryniscus including, but not limited to: fingers II, III, and V much reduced; nuptial pad with few enlarged, brown-colored spines on medial margin of finger II; seven presacral vertebrae, the last fused with the sacrum; and ventral humeral crest prominent, forming a spinelike projection. © Copyright © American Museum of Natural History 2012.